PENGGUNAAN MEDIA SOSIAL TERHADAP KARAKTER PESERTA DIDIK PADA MAPEL PAI DI SMA PGRI 1 JOMBANG - Ma'rifah Ulil Azmi; Emi Lilawati; Waslah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of social media use on students’ character in Islamic Religious Education learning at a senior high school in Jombang. The research employs a quantitative approach with a survey design involving seventy-seven eleventh-grade students as respondents. Data were collected using a structured questionnaire and analyzed through validity and reliability testing followed by hypothesis testing using a partial t-test and simple linear regression. The results show that social media use has a significant positive effect on students’ character, indicated by a calculated t value higher than the critical value and a significance level below the standard threshold. The regression coefficient demonstrates that the relationship between social media use and character development is positive, with a moderate to strong level of influence. These findings indicate that the use of social media, when properly guided within the learning process, can support the development of students’ character in accordance with educational and moral values.